DYNAMIC RESPONSE ANALYSIS OF THE GEAR TRANSMISSION SYSTEM OF WIND TURBINE UNDER VARIABLE LOAD - ZHANG JianYu; LI JiaJun; DU XiaoZhong (Jixie qiangdu)
According to the working characteristics of varying speed and varying load of wind turbines in the random wind field,and based on the combined wind speed model,the time-varying load caused by random wind speed is studied. Considering internal and external excitations of the gear transmission system of wind turbine,the dynamic equation of the system is derived by Lagrange-theory. The numerical method is used to simulate the dynamics performance of the gear transmission system of wind turbine,the vibration displacement and the meshing force in system which are influenced by time-varying input torque are got.The results can provide a theoretical reference for vibration characteristic analysis and structural optimization design of main drive train of wind turbine.